DIFFERENCES IN LEVELS OF ANXIETY AND DEPRESSION IN PATIENTS WITH CARDIOVASCULAR DISEASE BEFORE AND AFTER PARTICIPATING THE CARDIOVASCULAR REHABILITATION PROGRAM PHASE II - Renata, Catlyne; Sarvasti, Dyana; Wattimena, Inge (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2024)
Background: Cardiovascular disease continues to experience an increase in cases nationally and globally. Anxiety disorders and depression are psychological disorders that are often experienced by patients which can worsen the conditionher. Components in the phase II cardiovascular rehabilitation program can help increase functional capacity and improve psychological conditions (anxiety and depression) in patients with cardiovascular disease.Objective: This study aims to determine differences in levels of anxiety and depression in patients with cardiovascular disease before and after participating in the phase II cardiovascular rehabilitation program.Methods: The research uses analytical observational studies with technique total sampling in the medical records of patients with cardiovascular disease. HADS Questionnaire (Hospital Anxiety and Depression Scale) in the patient's medical records before and after participating in the phase II cardiovascular rehabilitation program will be compared using a comparative testWilcoxon two paired samples to determine differences in patient levels of anxiety and depression.Results: The largest distribution was found to be male patients, aged 51-60 years who suffered from CHD (Coronary Heart Disease) after CABG (Coronary Artery bypass Graft). This study shows that there are significant differences in levels of anxiety and depression in patients with cardiovascular disease before and after participating in the phase II cardiovascular rehabilitation program (p<0.001).Conclusion: A comprehensive phase II cardiovascular rehabilitation program can improve psychiatric conditions (anxiety and depression) in patients with cardiovascular disease.